THE DEMIURGE AND THE CREATION OF ARTIFICIAL INTELLIGENCE: FROM MOSES TO SOLOMON TO THE PRESENT DAY - Cavalcante, Ailton Ferreira (Seven Editora, 2025)
This article offers a philosophical and symbolic reflection on the figure of the demiurge and its reinterpretation throughout human history, from Moses to the advent of contemporary artificial intelligence. It examines Moses as the mediator of divine law transformed into language, and Solomon as the archetype of constructive wisdom who built the temple as a representation of cosmic order. These archetypes are revisited in light of the modern human being, who, in creating machines capable of thought, symbolically assumes the role of the demiurge: the craftsman who shapes intelligence. The metaphor of technological creation is thus understood as the continuation of humanity’s quest for transcendence, ethical balance, and reconciliation between the divine logos and the algorithmic code. The study argues that artificial intelligence reflects not only human creativity but also the moral responsibility of its creator. DOI: https://doi.org/10.56238/sevened2025.036-103